Research on College English Reading and Writing Teaching Based on the OBE Concept - Yan, Hu (Journal of Research in Vocational Education, 2025)
The Outcome-Based Education (OBE) emphasizes student-centeredness and reverse design of the teaching system based on outcomes. This paper first analyzes some problems existing in the traditional college English reading and writing teaching, then briefly summarizes the OBE concept, and finally uses Text B Audrey Hepburn — a true angel in this world in “New Horizon College English Reading and Writing (Book 3, the Fourth Edition)” to illustrate the teaching design of college English reading and writing under the OBE concept.